Effect of Menopause on the Increased Cardiovascular Risk Factors at Public Health Centers in Semarang Regency - Dedi Haswan; Indah Kurniawati; Jatmiko Susilo† (JURNAL KESEHATAN REPRODUKSI, 2025)
Background: Menopause potentially causes changes in metabolic disorders and atherosclerosis. This condition triggers cardiovascular disease (CVD) 16 times greater than breast cancer.Objective: This study aimed to identify the prevalence of CVD risk factors in Prolanis participants at the Semarang Regency Health Center.Methods: A cross-sectional study was conducted with 147 participants, who were selected from a group of 208 individuals who had undergone menopause and agreed to participate, and for whom complete data was available. Data on body mass index, blood pressure, random glucose levels, and cholesterol were collected from August to October 2025. Statistical analyses were then performed using one-way ANOVA and Pearson's correlation test.Results: The results showed that menopause and the age at first menopause were significantly different, while the differences and correlations between menopause and blood pressure, blood glucose, and lipid levels were not significant.Conclusion: The prevalence of metabolic syndrome (Met-S) in postmenopausal women increases with age. Menopause and Met-S had no significant differences and correlations, although women with Met-S showed a higher risk of CVD.